Opioids and cancer prognosis: A summary of the clinical evidence. (16th February 2021) - Ramirez, Maria F.; Gorur, A.; Cata, Juan P.
Highlights: Opium use is associated with an increased risk of cancer development. Prescription opioid use have not convincingly showed to increase the risk of new cancers. The mu opioid receptor could be used as an actionable target for the treatment of malignancies expressing the receptor. Abstract: Pain is a common and devastating symptom among cancer patients. It can be caused by the cancer itself or by certain therapies like surgery, radiation or chemotherapy. Opioids are the first line of treatment for moderate to severe cancer-related pain. Opioids alone or in combination with non-opioid analgesics and adjuvant medications are important components for pain management during the perioperative period for cancer patients. Opioids act on the μ-opioid receptor (MOR), which is expressed in cancer cells and non-malignant cells of the tumor microenvironment. Retrospective studies suggest an association between the expression of MOR in cancers and shorter survival. In addition, recent evidence suggests that opium use and prescription opioids can influence clinical oncological outcomes. In this review, we will summarize the clinical evidence regarding the effect of opioid administration and survival in patients with cancer as well as the current evidence involving MOR expression and cancer progression.